Enjoying and learning english through group work - Cabrera Guamán, Janeth; Cabrera Guamán, Sandra
The current educational project is about the application of a set of activities by means of methodological group strategies based on a Cooperative Learning. It is destined to generate and benefit the development of the English speaking skill, and also to foster and enhance interaction, free expression, and creativity among the students. In this way, students gain self-confidence and feel able to speak and use more the target language. This project was addressed and applied to students of the 8th grade at National Sinincay High School, the target group. Cooperative Group Work can be defined as a range of concepts and techniques for enhancing the value of student-student interaction. In this project, the English speaking skill, self - confidence, free expression and creativity were promoted when students interacted with their peers, or the members of their group to brainstorm, explain, question, problem-solve, share ideas, opinions, ask for and give information, etc. The cooperative techniques have shown their great effectiveness and success in the acquisition of a foreign language. The techniques used in this project are Jigsaw, Talking in Chips, Cooperative Stories, Brainstorming, Mix and Match, Cooperative Sequencing, Numbered Heads Together, Similarity Groups, Learning in Teams, Round Table, Think-Pair- Share. Pair Interview, Think -Pair- Check.